Automotive Purveyor / Ahmad Avizmuqri Mohd Shamsul - Ahmad Avizmuqri, Mohd Shamsul (2020)
Automotive purveyor is the store that sell automotive spareparts such as for cars and motorsycle. Automotive purveyor will give the best services to their customer. This company will try our best to perform so that we will achieved the 5 star rating from our customer. This company is based on Kota Bharu which is the first store and also as the start up for this business. This store is at cener of the city so all of the consumer get their parts here. The concept for this business is to achived the best selling store in this state. Also we need to work hard so that this company will known not in this country but also to the world. The parts we selling here is the most durable plug you can ever used. The reasons is we get this part from the most famous brand such as Yokohama, Enkei and etc. This brand i well known so the consumer that buy parts from us would not be less sure. For this business, our manager target all kind of market potential such as the retailer, the wholesale buyer and the consumer. This is because, if this company focused on one target for example the wholesale buyer. The other customer will left behind. By the mean of left behind is we would not give them the best services that we promoted to offer in this business. So thiss will ruined the images of this company. Also we did not want to take any risk for focusing on one market only. Competitive in the business is not new things. Competetive in the business is really a good thing. The reasons is, if our business have the competitor which is trying to compete with us. So we will make up our plan to manage how to beat the competitors in a business ways. Such as get a higher sale monthly. Also we can be a better company if we have the competitors because we will always find the way to beat our competitors. All in once, it can make us to reach our goal of sale that we targetted. The main thing that we focused on is the profit of this company. Our management team will hustle to achived the sale target so that we will get this company to keep on running. By this, we can conclude that every time we are in the meeting, we will set up the goal and the manager will rpovide us the works that to achieved the manager goal. The management team in this company is all the person who is listed in the organizational chart. The role in the chart has its own speciality. They will be focusing to their job just to achieved the goal given. This team is the main pole for this company. If one of the team is being trouble, the manager will replaced them because we would not take any risk to make Automotive Purveyor’s image being charcoal.